2022
DOI: 10.3389/fninf.2022.794342
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Long Non-coding RNA and Messenger RNA Based Molecular Networks and Pathways in the Subacute Phase of Traumatic Brain Injury in Adult Mice

Abstract: Traumatic brain injury (TBI) is a complex injury with a multi-faceted recovery process. Long non-coding RNAs (lncRNAs) are demonstrated to be involved in central nervous system (CNS) disorders. However, the roles of lncRNAs in long-term neurological deficits post-TBI are poorly understood. The present study depicted the microarray’s lncRNA and messenger RNA (mRNA) profiles at 14 days in TBI mice hippocampi. LncRNA and mRNA microarray was used to identify differentially expressed genes. Quantitative real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…GO and KEGG functional analyses showed that the DEGs in the mouse cortex post-TBI, in the YTHDF1-knockout group compared with the WT group, were primarily enriched in the regulation of neurotransmitter-related neuronal signalling pathways (neuroactive ligand-receptor interaction, glutamatergic synapse, axon guidance, and cAMP signalling pathway); response to inflammation (cell adhesion molecule signalling pathway); and the regulation of apoptotic process (calcium signalling pathway). These signalling pathways are involved in the pathophysiological processes post-TBI [ 51 , 52 , 53 , 54 , 55 , 56 ]. Among them, cell adhesion molecules play important roles in brain development, and maintaining synaptic structure, function, and plasticity [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…GO and KEGG functional analyses showed that the DEGs in the mouse cortex post-TBI, in the YTHDF1-knockout group compared with the WT group, were primarily enriched in the regulation of neurotransmitter-related neuronal signalling pathways (neuroactive ligand-receptor interaction, glutamatergic synapse, axon guidance, and cAMP signalling pathway); response to inflammation (cell adhesion molecule signalling pathway); and the regulation of apoptotic process (calcium signalling pathway). These signalling pathways are involved in the pathophysiological processes post-TBI [ 51 , 52 , 53 , 54 , 55 , 56 ]. Among them, cell adhesion molecules play important roles in brain development, and maintaining synaptic structure, function, and plasticity [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%